Percy Jackson and the last Olympian - Riordan, Rick. (London : Puffin, 2010)
When demonic cheerleaders invade his high school, Percy Jackson hurries to Camp Half Blood, from whence he and his demigod friends set out on a quest through the Labyrinth, while the war between the Olympians and the evil Titan lord Kronos draws near.
Keywords: Jackson, Percy -- (Fictitious character) -- Juvenile fiction; Gods, Greek -- Juvenile fiction; Fantasy fiction